Development of an optimal model for technique. Part 3 - head position and motion - Havriluk, R. (Swimming World Magazine, 2018)
This series of articles on developing an optimal model for technique began with addressing the concepts of bodysize and shape (SW July). Last month`s article (SW Aug) considered the impact of body rotation on body size and shape. This month`s article examines the effect of head position and motion on body rotation, and consequently, body size andshape. The head is critical because a slight variation in the non-breathing position or excess motion during breathing can impact resistance from the rest of the body.